Almost there : a twisted tale - Rochon, Farrah (New York : Disney-Hyperion, 2022)
In this reimagining of *The Princess and the Frog*, Tiana makes a different deal with Dr. Facilier that leads her down a dark and dangerous path where she must fight for her dreams, her city, and her happily ever after.
"What if Tiana made a deal that changed everything?"--Cover.
Keywords: Princesses -- Fiction; African American women -- Fiction; Restaurants -- Fiction; Wishes -- Fiction; Magic -- Fiction; Voodoo -- Fiction; Fairy tales -- Adaptations